2020
DOI: 10.1038/s41598-020-59012-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of group size, age and handling frequency on inter-male aggression in CD 1 mice

Abstract: Aggression in male mice often leads to injury and death, making social housing difficult. We tested whether (1) small group size, (2) early age of allocation to a group decreases aggression and 3) manipulation increases aggression in male mice. A 14wk study was performed to assess the following conditions in male CD-1/ICR mice: group size (1, 2, or 3), age at grouping (5 or 7wks), and manipulation (daily scruffing or minimal weekly handling). Wounds, body weights, food consumption, nest scores, sucrose consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Multiple factors tested in this model did not appear to be significant predictors of fighting despite past research suggesting otherwise. Of particular note was the lack of a significant effect of the number of mice in the cage, which previous studies have shown to be the key factor underlying increased aggression at higher stocking density 31,32 , but see 35 for a counter-example. Our failure to observe this effect may be related to our SOP for injured mice.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple factors tested in this model did not appear to be significant predictors of fighting despite past research suggesting otherwise. Of particular note was the lack of a significant effect of the number of mice in the cage, which previous studies have shown to be the key factor underlying increased aggression at higher stocking density 31,32 , but see 35 for a counter-example. Our failure to observe this effect may be related to our SOP for injured mice.…”
Section: Discussionmentioning
confidence: 96%
“…At the cage level, multiple studies suggest higher stocking densities increase aggression and fighting 31 34 , although recent work in modern caging systems complicates this story 35 . This effect seems to be driven not by cage size or density per se, but by the absolute number of mice in the cage 15 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Locomotion activities (horizontal, total distance traveled, number of movements, stereotypy counts) were significantly increased in neuronal-specific conditional p53 KO mice compared to wild-type mice [88]. In addition, individually housed mice had high nest scores, low body weight, and increased sucrose and food consumption [89]. These multiple factors may affect the contradictory phenotypes of p53 mice.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, different strains, sexes, ages, and housing conditions of mice can affect thermal preference. 37,58,59 For example, older (>11 months) CD-1s prefer warmer temperatures, whereas older C57BL/6 mice do not. Singly housed older CD-1s also prefer warmer conditions than group housed ones, while younger CD-1s did not differ in preference when housed individually or in groups.…”
Section: Discussionmentioning
confidence: 99%